Theoretical and methodological foundations of the analysis of the problems of the transport economy - G. L. Ilyukhina (Путеводитель предпринимателя, 2022)
Today the transport and logistics of the Russian Federation is facing a systemic challenge due to such two main points, among them the incessant packages of sanctions of Western countries and the increase in global international competition. There are also significant restrictions on economic growth in the Russian Federation, which are expressed by the insufficient development of the logistics industry. Currently, there are qualitative and volumetric characteristics of the transport area. In particular, its infrastructure does not allow solving the tasks of a constantly developing economy efficiently and in the right volume and meeting the demand of the innovative sector for high–quality logistics services. All of the above points require significant restructuring of logistics and transport of the Russian Federation on the right rails.